Neuroanatomical Basis of Swallowing disorders after Stroke: A Pilot Study - Gonzalez-Fernandez, Marlis (2008)
BACKGROUND: Dysphagia is a common problem after stroke associated with significant morbidity and mortality. Except for patients with brain stem strokes, particularly lateral medullary strokes, it is difficult to predict which cases are likely to develop swallowing dysfunction based on their neuroimaging. Clear models of swallowing control and integration of cortico-bulbar input have not been defined and the role of subcortical structures is unclear. OBJECTIVE: To identify supratentorial regions of interest (ROIs) that might be related to clinically important dysphagia in acute stroke patients, focusing on subcortical structures. METHODS: We studied 29 acute supratentorial ischemic stroke cases admitted to our institution between 2001 and 2005 diagnoses with first ischemic stroke and without history of swallowing dysfunction. Subjects had magnetic resonance imaging within 24 hours. Cases were defined as those subjects who were diagnosed as dysphagic after clinical evaluation by a speech language pathologist (SLP) and whose dysphagia was considered clinically significant i.e., requiring treatment by diet modification. Controls were defined as those patients who: (1) passed the stroke unit’s dysphagia screening, (2) had a clinical evaluation by SLP that did not result in a diagnosis of dysphagia or diet modifications, or (3) had no documented evidence of dysphagia evaluation or treatment during hospitalization and were discharged on a regular diet. A trained technician, blinded to case-control status, examined 12 ROIs for dysfunctional tissue in diffusion and perfusion-weighted images. The odds ratio (OR) of dysphagia was calculated for each ROI. Logistic regression models were used to adjust for stroke severity (NIHSS) and volume. RESULTS: Analysis of data on 14 cases and 15 controls demonstrated significant differences in the unadjusted odds of dysphagia for the following ROIs: 1) primary somatosensory, motor and motor supplementary areas (PSSM) (OR=10, p=0.009); 2) orbitofrontal cortex (OFC)(OR=6.5, p=0.04); 3) putamen, caudate, basal ganglia (PCBG)(OR=5.33, p=0.047); and 4) internal capsule (IC)(OR=26; p=0.005). Non-significant differences were found in the insula and temporopolar cortex. Adjusted OR of dysphagia for subjects with strokes affecting the IC was 17.8 (p=0.03). Adjusted odds ratios for the PSSM, OFC, and PCBG were not statistically significant. CONCLUSION: Significantly increased odds of dysphagia were found in subjects with IC involvement. Other supratentorial areas that may be associated with dysphagia include the PSSM, OFC, and PCBG. Analysis of additional areas was limited by the number of subjects in our sample. Future studies with larger sample size are feasible and will contribute to the development of a full swallowing control model.